2016
DOI: 10.1111/jpn.12540
|View full text |Cite
|
Sign up to set email alerts
|

Physiological limit of the daily endogenous cholecalciferol synthesis from UV light in cattle

Abstract: The link between UV light (sunlight) and endogenous cholecalciferol (vitamin D ) synthesis in the skin of humans has been known for more than a 100 years, since doctors for the first time successfully used UV light to cure rickets in children. Years later, it was shown that UV light also had a significant effect on the cholecalciferol status in the body of cattle. The cholecalciferol status in the body is measured as the plasma concentration of 25-hydroxycholecalciferol, which in cattle and humans is the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
3
7
0
1
Order By: Relevance
“…Considering therefore that the difference in 25vitD status between the groups was not caused by a different degradation and the husbandry conditions and the feeding were identical for all groups, the difference must have been caused by the production with irradiation of the skin. These findings are in line with previous studies that showed a better vitD status in sheep exposed to UVB irradiation (Quarterman et al, 1964;Smith and Wright, 1980;Hidiroglou and Karpinski, 1989;Kovács et al, 2015) and show evidence of the parallelism to the endogenous vitD production in dairy cows (Hymøller et al, 2009;Jensen, 2010, 2012;Hymøller et al, 2017). Also, the lower content of 7DHC in the skin of the irradiated animals compared with the control group supports our hypothesis.…”
Section: Mnsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering therefore that the difference in 25vitD status between the groups was not caused by a different degradation and the husbandry conditions and the feeding were identical for all groups, the difference must have been caused by the production with irradiation of the skin. These findings are in line with previous studies that showed a better vitD status in sheep exposed to UVB irradiation (Quarterman et al, 1964;Smith and Wright, 1980;Hidiroglou and Karpinski, 1989;Kovács et al, 2015) and show evidence of the parallelism to the endogenous vitD production in dairy cows (Hymøller et al, 2009;Jensen, 2010, 2012;Hymøller et al, 2017). Also, the lower content of 7DHC in the skin of the irradiated animals compared with the control group supports our hypothesis.…”
Section: Mnsupporting
confidence: 93%
“…The animals in this study had a normal initial vitD status thanks to the high vitD intake due to the vitD content in the normal concentrate fed before starting the experiment and the vitD intake via milk before weaning. Indeed, for newborn ruminants, in contrast to other species, milk can be an adequate source of vitD under the condition of a high vitD status in combination with a moderate milk yield of the dam (Kohler et al, 2013;Weiss et al, 2015;Hymøller et al, 2017). The 25vitD can then be stored in the body tissue (primary fat, muscle, and liver) to help prevent a fast drop of vitD status (Hidiroglou, 1987;Hidiroglou and Karpinski, 1989).…”
Section: Mnmentioning
confidence: 99%
“…Cows produce vitamin D 3 in the skin in response to UV exposure, as was recently shown in cows not supplemented with cholecalciferol for 6 mo and exposed to UV light for 30, 90, or 120 min/d for 28 d (Hymøller et al, 2017). Exposure to UV light increased plasma concentrations of 25-hydroxyvitamin D 3 linearly from approximately 5 ng/mL on experiment d 0 to almost 40 ng/mL on d 28 in cows receiving either 90 or 120 min/d of light exposure (Hymøller et al, 2017). Therefore, some background concentration of vitamin D metabolites was expected in cows from endogenous synthesis or from previous supplementation before initiation of the experiment.…”
Section: Pre-and Postpartum Concentrations Of Metabolitesmentioning
confidence: 74%
“…Multiple factors are known to regulate Vit D 3 skin synthesis, including latitude, altitude, and time of exposition to sunlight 23 . As in humans, seasonal variation in the Vit D status on grazing calves (with minimal or null Vit D 3 supplementation) has been reported, with low 25OHD concentration in winter and early spring 21 , 24 .…”
Section: Discussionmentioning
confidence: 99%